Network analyses elucidate the role of SMYD3 in esophageal squamous cell carcinoma. Issue 8 (3rd July 2017) - Liu, Xinning; Zheng, Zhoude; Chen, Chuhong; Guo, Simin; Liao, Zhennan; Li, Yue; Zhu, Ying; Zou, Haiying; Wu, Jianyi; Xie, Wenming; Zhang, Pixian; Xu, Liyan; et al.
Abstract : SMYD3 is a member of the SET and myeloid‐Nervy‐DEAF‐1 (MYND) domain‐containing protein family of methyltransferases, which are known to play critical roles in carcinogenesis. Expression of SMYD3 is elevated in various cancers, including esophageal squamous cell carcinoma (ESCC), and is correlated with the survival time of patients with ESCC. Here, we dissect gene expression data, from a previously described KYSE150 ESCC cell line in which SMYD3 had been knocked down, by integration with the protein–protein interaction (PPI) network, to find the new potential biological roles of SMYD3 and subsequent target genes. By construction of a specific PPI network, differentially expressed genes (DEGs), following SMYD3 knockdown, were identified as interacting with thousands of neighboring proteins. Enrichment analyses from the DAVID Functional Annotation Chart found significant Gene Ontology (GO) terms associated with transcription activities, which were closely related to SMYD3 function. For example, YAP1 and GATA3 might be a target gene for SMYD3 to regulate transcription. Enrichment annotation of the total DEG PPI network by GO 'Biological Process' generated a connected functional map and found 532 significant terms, including known and potential biological roles of SMYD3 protein, such as expression regulation, signal transduction, cell cycle, cell metastasis, and invasion. Subcellular localization analyses found that DEGs and their interacting proteins were distributed in multiple layers, which might reflect the intricate biological processes at the spatial level. Our analysis of the PPI network has provided important clues for future detection of the biological roles and mechanisms, as well as the target genes of SMYD3. Abstract : Expression of the methyltransferase SMYD3 is correlated with survival time in esophageal cancer patients. Differentially expressed genes (DEGs), obtained from the microarray experiment following SMYD3 knockdown in esophageal cancer cells, were used to construct a protein–protein interaction network, following various functional annotation analyses. These results will provide important clues for future detection of the biological roles and mechanisms as well as the target genes of SMYD3.